The effect of eight weeks high intensity interval training on the expression of cardiac miRNA-21 and miRNA-1 in wistar male rats - Sohrab Ghalehgir; Javad Vakili; Mostafa Khani; Karim Azali Alamdari (فیزیولوژی ورزش و فعالیت بدنی)
Background and Purpose: microRNA (miRNA) are a new class of biomarkers that are involved in many biological processes and gene expression. Also, High-intensity exercise training (HIIT) has long been demonstrated to help improve cardiorespiratory fitness and corresponding physiological variables in healthy individuals. The training involves repeated short to long bouts of relatively high-intensity exercise alternating with recovery periods of low-intensity activity or passive rest. Thus, the present study examined the effect of eight weeks of high intensity interval training (HIIT) on the expression of miRNA-21 and miRNA-21 in male rats.Materials and Methods: In this experimental study, twenty adult Wistar male rats were selected and randomly divided into two groups: control and HIIT (T) protocols. Accordingly, the rats underwent the HIIT program on smart electronic tape recorders for eight weeks, five days a week. HIIT training was performed with an intensity of 85-90% of maximum speed in 6-12 times for two minutes and with 3-minute active rest intervals with an intensity of 30% VO2max. At the end of the study contract, all mice were anesthetized and operated 48 hours after the last intervention without painless method to determine changes in miR-1 and miR-21 gene expression by real-time PCR in left ventricular tissue. To investigate the normality of data distribution, Shapiro-Wilk test and to test the hypotheses, two-way analysis of variance was performed at a significance level of P > 0.05 with SPPS26 statistical software.Results: miRNA-21 expression were significantly higher after eight weeks HIIT than control groups (P < 0.05). However, miRNA-1 expression were significantly lower after eight weeks HIIT than control groups (P < 0.05).Conclusion: It seems that changes in the tissue level of miRNA-21 and miRNA-1 expression are related to the signaling pathways of adaptations related to exercise training.